The Measure of Finality: A Dialectical Analysis of Legitimacy Concerns in International Investment Arbitration - Dr. Stefan Mandelbaum (UCL Journal of Law and Jurisprudence, 2020)
To download this paper, please click here. Over the last two decades, the institution of investment treaty arbitration has increasingly attracted a particular type of academic criticism. In challenging the overall coherence of an international adjudicative social practice, the spectre of a legitimacy crisis has successively established itself in the scholarly language-game orbiting investor-State dispute settlement. This article offers a structural explanation of legitimacy concerns by exploring the epistemic framework within which legitimacy issues materialise. On the basis of a dialectical analysis, it is argued that legitimacy challenges are intrinsically linked to evaluations of performances of arbitral reasoning, in particular, and to the epistemic condition of the doctrine of finality in general. Procedural autonomy (contract) and the latent dependency of proceedings on State authorities (adjudication) will be conceptualised as the two defining moments underlying the doctrine of finality. The article concludes by applying the developed analytical template of finality as a measure of legitimacy in order to review the legal reasoning in the two cases of Lauder/CME v The Czech Republic, as well as in Ampal-American and Others v Egypt, paradigmatic instances of concurrent treaty arbitration proceedings.